Taxonomic and Evolutionary Significance of Peptides in Amphibian Skin - Cei, José Miguel Alfredo María (1985)
A tentative approach to the systematic distribution of active peptides in the anuran cutaneous tissue is presented. Eleven peptide groups have been so far detected in the frog skin. The occurrence of seven major groups in different Archaeo-, Meso-, and Neo-batrachian amphibian stocks is briefly discussed. Tachykinins and caeruleins have been isolated from some Mesobatrachian (Xenopus) and old Neobatrachian families, even of Gondwanian ancestry, such as leptodactylids, myobatrachids, pelodryadids and ranids. A more widespread systematic distribution is reported for bradykinins and bombesins, occurring in Archaeobatrachian and Neobatrachian frogs, represented by several primitive families both of Laurasian and Gondwanian origin: among them are liopelmatids, discoglossids, myobatrachids, pelodryadids, heleophrynids and ranids. The unique position of Neotropical phyllomedusid frogs, a peculiar hylid stock with ancestral leptodactylid and myobatrachid affinities is emphasized. As many as seven major peptide groups are present in these specialized climbing anurans: tachykinins, caeruleins, bombesins, bradykinins, sauvagine, dermorphins, tryptophyllins. Phyllomedusid frogs appear to display the highest adaptive level yet reached in the peptide biochemical evolution of the amphibian skin.